Comparison of renin and catecholamine release in patients undergoing eversion or conventional carotid endarterectomy - Demirel, Serdar; Macek, Laura; Attigah, Nicolas; Hakimi, Maani; Able, Thomas; Böckler, Dittmar (Journal of vascular surgery, 2012)
Objective: The two techniques for carotid endarterectomy (CEA)— conventional (C-CEA) and eversion (E-CEA)— have different effects on blood pressure. This study compared sympathetic activity after C-CEA and E-CEA, as measured by renin and catecholamine levels. Methods: E-CEA (n ؍ 40) and C-CEA (n ؍ 34) were performed in 74 patients with high-grade carotid stenosis. The choice of technique was made at the discretion of the operating surgeon. All patients received clonidine (150 ␮g) preoperatively. Regional anesthesia was used. The carotid sinus nerve was transected during E-CEA and preserved during C-CEA. Renin, metanephrine, and normetanephrine levels were measured preoperatively and at 24 and 48 hours postoperatively. Results: Compared with baseline, levels of renin, metanephrine, and normetanephrine decreased at 24 and 48 hours after C-CEA (P < .0001). After E-CEA, however, renin and normetanephrine levels were unchanged at 24 hours, and metanephrine levels were increased (P < .0001). At 48 hours, levels of renin (P ؍ .04), metanephrine (P < .0001), and normetanephrine (P ؍ .02) were increased. Compared with C-CEA, E-CEA was associated with signiﬁcantly increased sympathetic activity at 24 and 48 hours (P < .0001). Although the use of vasodilators for postoperative hypertension did not differ in the postanesthesia care unit (E-CEA 35% vs C-CEA 18%, P ؍ .12), vasodilator use on the ward was more frequent after E-CEA (60% vs 32%, P ؍ .02). Conclusions: E-CEA appears to be associated with greater postoperative sympathetic activity and vasodilator requirements than C-CEA, ﬁndings likely related to sacriﬁce of the carotid sinus nerve during E-CEA but not C-CEA. ( J Vasc Surg 2012;56:324-33.)